Analysis of endocrine hormone metabolism level in a Chinese patient with mucopolysaccharidosis IVA: A case report. Issue 38 (September 2018) - Xu, Linxin; Ren, Yi; Yin, Jianhong; Yang, Jing; Liu, Yunfeng; Zhang, Jin; Zhang, Yi; Xiang, Chenyu; Yang, Luyang
Abstract: Rationale: Mucopolysaccharidosis IVA (Morquio A) is a catabolic mucopolysaccharide disorder caused by galactose-6-sulfate sulfatase deficiency. It is an autosomal recessive inherited disease. Previous reports on clinical characteristics of Morquio A mainly focused on growth retardation, skeletal deformities, and organ damage in children and adolescents, while the effects of mucopolysaccharide metabolism disorders on endocrine hormone metabolism level have not been reported. Herein, we reported the endocrine hormone metabolism in a case diagnosed as Morquio A. Patient concerns: The patient was a 17-year-old girl with growth retardation, hearing loss, and severe skeletal dysplasia(scoliosis and chicken breast), and was evaluated to have normal nervous system function and intelligence by physicians. Diagnoses: She was diagnosed as Morquio A based on gene analysis, mucopolysaccharide-related enzymes and her clinical features. Interventions: The patient didn't accepted the enzyme replacement therapy. Outcomes: She had a homozygous mutation of the GALNS gene. The b-glucuronidase content in the blood was reduced. The serum sodium, serum adrenocorticotropic hormone, and cortisol rhythms (8 AM) were decreased. The levels of PRA(plasma renin activity), PAII(plasma angiotensin II), and PALD(plasma aldosterone) were elevated. Bone mineral density suggests osteoporosis. There were no abnormalities in bone metabolism indicators, growth hormone, thyroid hormone, and sex hormones. In summary, the level of endocrine hormones in patients with mucopolysaccharidosis IV changes. Lessons: This is the report on endocrine hormone level in a patient with mucopolysaccharidosis IV in China. Due to the disease may have relatively incomplete adrenal function, which provides a basis for future understanding and diagnosis of this disease.